The population, utilization and local management of Elaeodendron transvaalense in the Blouberg Municipality, Limpopo Province, South Africa - Marula Triumph Rasethe; Sebua Silus Semenya (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Rasethe MT, Semenya SS. 2019. The population, utilization and local management of Elaeodendron transvaalense in the Blouberg Municipality, Limpopo Province, South Africa. Biodiversitas 20: 2978-2985. Elaeodendron transvaalense is highly harvested by rural communities of the Limpopo Province (South Africa) to meet various livelihoods. However, its information on the population, uses, harvesting practices, threatening factors and local management is still not investigated and documented in many parts of this province. The current study therefore, provides a base-line data of E. transvaalense occurring in two villages of the Blouberg Municipality, Limpopo Province. Data on the population locations, utilization and local management strategies of this species was collected from community members, traditional healers and leaders via semi-structured questionnaires, supplemented by field observations on harvesting practices, threats, area of occupancy, population size, density and demographic structure and population health. Two populations, referred in this study as Sebotlana and Makgabeng covering an area of 25252.17 m2 and 45099.79 m2, respectively, were located in the two villages of the Blouberg Municipality. Both populations were characterized by a mixture of healthy seedlings, sapling, juvenile, middle trees, adult trees, and senescent trees, with Makgabeng population having the highest plant density. Various morphological parts such as bark and roots were mainly used by respondents as common ingredients in traditional medicines, mainly for cough, fever, diarrhoea, symptoms of AIDS and as blood purifier. Evidence of harvesting was only observed on Sebotlana population, which was also highly impacted by rural settlement expansion. Overall, there were no local management strategies meant specifically for the identified E. transvaalense around the Blouberg area.